PENERAPAN SANKSI TERHAOAP PELANGGARAN PPTKIS DALAM PRA PENEMPATAN TKI DI LUAR NEGERI - , Ari Hernawan, dan Supriyadi. ([Yogyakarta] : Fak. Hukum UGM, 2007)
Act 39 of 2004 concerning Placement and Protection of Indonesian Labor in Foreign Country has detf!rmined and regulated sanction that can be deliveredfor violation by Private Indonesian Labor Placement Agency (PPTKlS) in worker pre-placement inforeign country. The sanction includes administrative sanction and criminal sanction. This research was intended to study enforcement of administrative and criminal sanction for violation of PPTKlS in labor placement inforeign country and resettlement of dispute between PPTKIS and TKI candidate in relation to placement agreement. The results of the research indicated that there was violation by PPTKIS in pre-placement in foreign country. The violation was on recruitment of labor candidates. PPTKlS did not ask approval from institution responsible for employment about recruitment information. Indonesian Labor Service and Placement Office (BP2TKl) have delivered written warn